Positive correlation between serum and peritoneal fluid CA-125 levels in women with pelvic endometriosis - Amaral, Vivian Ferreira do; Ferriani, Rui Alberto; Sá, Marcos Felipe Silva de; Nogueira, Antonio Alberto; Silva, Julio César Rosa e; Silva, Ana Carolina Japur de Sá Rosa e; Moura, Marcos Dias de (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: One of the diag- nostic markers of endometriosis is CA-125, and elevated levels of this are caused by high concentrations in the ectopic endometrium. The objective of this study was to correlate CA-125 levels in serum and peritoneal fluid from women with and without pelvic endometriosis. DESIGN AND SETTING: This was a prospective, cross-sectional, controlled study of consecutive patients undergoing laparoscopy for infertility, pelvic pain or tubal ligation, during early follicu- lar phase, at the university hospital of Faculdade de Medicina de Ribeirão Preto. METHODS: Fifty-two patients were divided into two groups: endometriosis group, consisting of 35 patients with biopsy-confirmed pelvic endo- metriosis, and control group, consisting of 17 patients without endometriosis. CA-125 levels in serum samples and peritoneal fluid were determined by chemiluminescence. RESULTS: CA-125 levels in serum and peritoneal fluid were higher in patients with advanced pel- vic endometriosis (means of 39.1 ± 45.8 U/ml versus 10.5 ± 5.9 U/ml in serum, p < 0.005; 1,469.4 ± 1,350.4 U/ml versus 888.7 ± 784.3 U/ml in peritoneal fluid, p < 0.05), and showed a positive correlation between each other (correlation coefficient (r) = 0.4880). Women with more advanced degrees of endometriosis showed higher CA-125 levels in both serum and peritoneal fluid (p = 0.0001). CONCLUSION: There is a positive correlation between serum and peritoneal fluid values of CA-125 in women with and without endome- triosis, and their levels are higher in peritoneal fluid. Advanced endometriosis is related to higher levels in both serum and peritoneal fluid.